Effectiveness of Information Technology (SIAK) in Population Administration Services in Rejomulyo Village, Panekan District, Magetan Regency - Dhani Muhammad, Rizki; Dharmala, Bayu (Internasional Journal of Politics and Public Policy, 2025)
This study analyzes the effectiveness of the Population Administration Information System (SIAK) in population administration services in Rejomulyo Village, Panekan District, Magetan Regency. Using descriptive qualitative methods through interviews, observation, and documentation, this study examines five indicators of effectiveness: productivity, quality, efficiency, flexibility, and satisfaction. The results show that SIAK has increased the productivity of population data management with a faster and more organized process. Service quality has improved significantly, evidenced by the administration compliance award from 2021 to 2024. Time efficiency has increased drastically from days to 15-30 minutes, saving transportation costs and community labor. Flexibility is demonstrated through the adaptation of village officials to new technologies and the appointment of dedicated operators. The level of community satisfaction has increased thanks to easy access and speed of service. Challenges faced include limited human resources and the condition of computer equipment. This study concludes that the implementation of SIAK in Rejomulyo Village has been effective in improving the quality of population administration services to the community.